The Optimization Of Employee Stock Option Plan In Achieving Financial Performance - Nur Fadjrih Asyik (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This study aimed to examine the effects of Intellectual Capital proxied by Human Capital (HC), Structural Capital (SC), and Customer Capital (CC) on the company's financial performance. It also investigated stock-based compensation's impact through employees' stock options programs and Intellectual Capital on the company's economic performance. The research samples were 36 companies that implemented the Employee Stock Option Plans as a compensation scheme during the 2016-2019 period. There were 144 observations. The partial test used multiple regression, while the moderating variable test applied residual analysis by examining the effect of deviation from a model. As a result, this study indicated that Human Capital partially influenced its financial performance. Stock-based compensation impacts the effect of Human Capital on financial performance. The shares ownership of employees with competencies, knowledge, skills, and behavior will support organizational structures' optimization in achieving work performance. Human capital is the source of innovation and knowledge that can solve a company’s problems. The implication of this research is that information about intellectual capital (Human Capital, Structural Capital, and Employee Capital) is needed by the company to determine the effectiveness of implementing the employee stock option plan in achieving better wealth in the future.